Pudendal nerve block approach for children undergoing urethroplasty - Annemarie Chrysantia Melati; Andi Ade Wijaya (Urology Case Reports)
This case presents the perioperative management of a 6-year-old male patient undergoing penoscrotal urethroplasty. General anesthesia was administered along with Fentanyl (1–2 mcg/kgBW) during induction Bilateral pudendal nerve blocks were performed using Bupivacaine 0.25 % with no additional opioids required during the surgery, and hemodynamic stability was maintained. Postoperative pain was effectively managed with paracetamol, and the patient was discharged on the second postoperative day without any complications. This case highlight the use of pudendal nerve block as a safe and effective analgesic thecnique for pediatric urethroplasty.